Islamic medical education revisited: conceptual and practical aspects - Sharifudin, Mohd Ariff; Ayeop, Mohd Adham Syah; Shahar, Mohammad Arif; Che Mohamad, Che Anuar; Md Tahir, Mohd Faiz; Idris, Mohd Faiz (2016)
Even after more than two decades, the concept of Islamic Medicine is still widely debatable. While some intellectuals proclaimed that the treasury of medical knowledge was forfeited by the West from the Muslim Civilization, one could not deny that in the current modern civilization, Westerns are far ahead than Muslims in many aspects. The urge to revive the Muslim Civilization has lead towards the drive for Islamization of human knowledge. The call for Islamic Medicine, as part of the Islamization movement, has taken its course into two different directions: Islamic Medicine as an alternative to the Western Medicine, and a call towards integrating the Islamic values into the current accepted medical system. Further confusions were raised with the argument of which terminology is more practical and compliable, Islamization or Islamicisation, with the former may bring about the idea of conversion rather than integration. The term Islamic Medical Practice (IMP), widely used in various medical institutions, is a burden upon Muslim medical academicians, in which majority of them perceived as being incompetent to deliver the tasks. In Kulliyyah of Medicine IIUM, the term “Islamic input in Medical Practice” (IIMP) is preferred. It gives a broader approach in integrations of Islamic teachings in medical education, in line with the Islamization guidelines outlined by the University. This review discusses the concept and practical approach that can be offered by medical academicians of various backgrounds in contributing towards the vision and mission of the University.